Graphene composite material and preparation method thereof
By combining graphene oxide, magnetic particle powder and single-wall carbon nanotubes, a sponge framework structure is formed, and acetylene gas is introduced during the preparation process to deposit an amorphous carbon layer to cover the graphene surface, the problem of poor impedance matching of existing graphene matrix materials is solved, and the absorption efficiency and structural stability of the material are significantly improved.
Patent Information
- Application Number
- CN202510309235.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-17
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-03-17
AI Technical Summary
The microwave absorption performance of existing graphene matrix materials mainly depends on dielectric loss, resulting in poor impedance matching and low absorption efficiency.
By combining graphene oxide, magnetic particle powder and single-wall carbon nanotubes, a sponge framework structure is formed, and acetylene gas is introduced during the preparation process, and an amorphous carbon layer is deposited to cover the graphene surface, enhancing the dielectric and hysteresis loss of the material.
The absorption efficiency and structural stability of graphene composite materials are improved, the impedance matching between dielectric loss and hysteresis loss is enhanced, and the electromagnetic absorption capacity of the material is significantly improved.
Smart Images

Figure CN119822362A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of wave absorbing materials, and in particular to a graphene composite material and a preparation method thereof. Background Art
[0002] In recent years, with the development of electronic devices such as mobile phones and computers, the electromagnetic interference problem caused by electromagnetic waves has become more and more serious. The application of absorbing materials can effectively alleviate electromagnetic interference. Its absorption mechanism is to convert the energy of the incident wave into other forms of energy, such as heat energy. This energy conversion is caused by the magnetic loss and dielectric loss of the absorbing material. Therefore, in order to improve the electromagnetic absorption capacity, it is necessary to achieve good impedance matching of magnetic loss and dielectric loss. As a new type of carbon-based material, graphene has been widely studied due to its unique advantages of high dielectric loss and low density. However, as a non-magnetic material, the microwave absorption performance of graphene is mainly attributed to its dielectric loss, resulting in poor impedance matching. Therefore, how to improve the absorption efficiency of graphene matrix materials is an urgent problem that needs to be solved. Summary of the invention
[0003] The embodiment of the present application provides a graphene composite material and a preparation method thereof, wherein the graphene composite material has both high structural stability and high wave absorption efficiency. The technical solution is as follows: In one aspect, a method for preparing a graphene composite material is provided, the preparation method comprising: preparing a graphene oxide dispersion; Adding magnetic particle powder and single-walled carbon nanotubes into the graphene oxide dispersion to obtain a first mixed solution; Concentrating and freezing the first mixed solution to obtain a first composite material; annealing the first composite material to obtain a second composite material; The second composite material is placed in a carbonization furnace, heated for a first time under a nitrogen atmosphere, and transferred to a rotary kiln after cooling, wherein the temperature of the rotary kiln is 500-560° C.; Acetylene gas is introduced into the rotary kiln, and after reacting for a second time period, a graphene composite material is obtained.
[0004] In a possible implementation, the preparation of the graphene oxide dispersion includes: Mixing graphite powder, sodium nitrate and concentrated sulfuric acid, and stirring in an ice bath to obtain a second mixed solution; adding potassium permanganate to the second mixed solution to obtain a third mixed solution; Deionized water and hydrogen peroxide are added dropwise to the third mixed solution, and the mixture is washed until the pH value is 4 to 7 to obtain the graphene oxide dispersion.
[0005] In another possible implementation, the mass of the graphite powder is 100-500 g, the mass of the sodium nitrate is 50-200 g, the volume of the concentrated sulfuric acid is 1-3 L, the mass of the potassium permanganate is 300-600 g, the volume of the deionized water is 15-25 L, and the volume of the hydrogen peroxide is 2-8 L.
[0006] In another possible implementation, the first mixed solution is concentrated and frozen to obtain a first composite material, including: Concentrating the first mixed solution, wherein the viscosity after concentration is 3000-10000 mPa·S; The concentrated first mixed liquid is transferred to a preset plate mold and frozen and formed by liquid nitrogen; The first composite material is obtained by removing moisture from the first mixed solution after freeze-setting using a freeze-drying process.
[0007] In another possible implementation, the process conditions of the freeze-drying process are: vacuum degree of 40~100 Pa, freezing temperature of -80~-50°C, and cooling rate of 5~15°C / min.
[0008] In another possible implementation, the process conditions of the annealing treatment are: annealing temperature is 400-800° C., holding time is 4-8 hours, and cooling rate is 5-15° C. / min.
[0009] In another possible implementation, the mass of the magnetic particle powder is 10-100 g, the mass of the single-walled carbon nanotube is 8-50 g, and the volume of the graphene oxide dispersion is 2-5 L.
[0010] In another possible implementation, the magnetic particle powder includes at least one of nano iron powder and ferroferric oxide powder.
[0011] In another possible implementation, the heating temperature in the carbonization furnace is 500-650° C., and the first time length is 4-8 hours; The flow rate of the acetylene gas is 1-5 L / min, and the second time length is 6-10 hours.
[0012] On the other hand, a graphene composite material is provided, wherein the graphene composite material is prepared by any of the preparation methods described above.
[0013] The present application embodiment provides a method for preparing a graphene composite material, which uses graphene oxide, magnetic particle powder and single-walled carbon nanotubes to prepare the composite material, and acetylene gas is introduced during the preparation process. Wherein, graphene and single-walled carbon nanotubes constitute a sponge skeleton material, and the magnetic particle powder is filled in the skeleton gap. Compared with a single skeleton, the skeleton composed of graphene and carbon nanotubes is more stable, and graphene and carbon nanotubes simultaneously construct a planar and vertical conductive network, which can accelerate the migration of carriers and effectively enhance the dielectric loss of the material. The magnetic particle powder is also conducive to improving the hysteresis loss of the material, and the sponge-like substrate has a large number of pore structures, which is conducive to extending the absorption path of electromagnetic waves, improving the electromagnetic wave absorption efficiency, and thus improving the absorption capacity of the material. At the same time, acetylene can be deposited in the gaps on the surface of the material after cracking, and the surface defects and uncovered pores of graphene are repaired or coated by an amorphous carbon layer, and the amorphous carbon layer can effectively prevent the skeleton structure from directly contacting water or other corrosive substances, and maintain the stability of the internal structure. It can be seen that the graphene composite material prepared by this method has both high structural stability and high wave absorption efficiency.
[0014] It is to be understood that the foregoing general description and the following detailed description are exemplary only and are not restrictive of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a flow chart of a method for preparing a graphene composite material provided in an embodiment of the present application; Figure 2 This is a TEM morphology image of a graphene material prepared in a comparative example provided in an embodiment of the present application; Figure 3 This is a TEM morphology image of a graphene composite material prepared in Example 3 provided in the examples of the present application; Figure 4 1 is a schematic diagram of a reflectivity test of a graphene composite material prepared in Examples 1 to 5 and a graphene material prepared in a comparative example provided in an embodiment of the present application; Figure 5 1 is a schematic diagram of the real part of the complex dielectric constant and the frequency, in which the graphene composite materials prepared in Examples 1 to 5 and the graphene materials prepared in the comparative example are tested for the complex dielectric constant provided in the examples of the present application; Figure 6 1 is a schematic diagram of the complex dielectric constant imaginary part and frequency of a graphene composite material prepared in Examples 1 to 5 and a graphene material prepared in a comparative example provided in an embodiment of the present application; Figure 71 is a schematic diagram of the real part of magnetic permeability and frequency, in which the magnetic permeability of the graphene composite material prepared in Examples 1 to 5 and the graphene material prepared in the comparative example are tested in the embodiments of the present application; Figure 8 The present application provides an embodiment of a magnetic permeability test of a graphene composite material prepared in Examples 1 to 5 and a graphene material prepared in a comparative example, and shows a schematic diagram of the imaginary part of the magnetic permeability and the frequency. DETAILED DESCRIPTION
[0016] In order to make the technical solutions and advantages of the present application clearer, the implementation methods of the present application are described in further detail below.
[0017] On the one hand, the present invention provides a method for preparing a graphene composite material. Figure 1 , the preparation method comprises: Step 101: Prepare a graphene oxide dispersion.
[0018] This step can be achieved by following the steps (1) to (3), including: (1) Graphite powder, sodium nitrate and concentrated sulfuric acid are mixed and stirred in an ice bath to obtain a second mixed solution.
[0019] Among them, the mass of graphite powder is 100~500g, the mass of sodium nitrate (NaNO3) is 50~200g, the concentration of concentrated sulfuric acid is 98%, and the volume is 1~3L.
[0020] The mass of graphite powder can be 100g, 150g, 200g, 250g, 300g, 350g, 400g, 450g, and 500g, the mass of NaNO3 can be 50g, 80g, 100g, 150g, and 200g, and the volume of 98% concentrated sulfuric acid can be 1L, 1.2L, 1.5L, 1.8L, 2L, 2.5L, and 3L.
[0021] The stirring time in step (1) can be 0.5 to 2 hours, for example, the stirring time is 0.5 hours, 1 hour, 1.5 hours, or 2 hours. In the embodiments of the present application, only the stirring time of 1 hour is used as an example for description.
[0022] (2) Add potassium permanganate to the second mixed solution to obtain a third mixed solution.
[0023] Add potassium permanganate (KMnO4) to the second mixed solution and continue stirring for 1 to 3 hours to obtain a third mixed solution.
[0024] The mass of KMnO4 is 300-600 g. Specifically, the mass of KMnO4 can be 300 g, 350 g, 400 g, 450 g, 500 g, 550 g, or 600 g.
[0025] The stirring time in step (2) can be 1 h, 1.5 h, 2 h, 2.5 h, or 3 h. In the embodiments of the present application, only a stirring time of 2 h is used as an example for illustration.
[0026] It should be noted that after obtaining the third mixed solution, the third mixed solution can be stored at 25-35° C. for 20-40 min before performing step (3).
[0027] Among them, the storage time can be 20min, 25min, 30min, 35min, 40min, and the storage temperature can be 25℃, 28℃, 30℃, 32℃, 35℃.
[0028] (3) Deionized water and hydrogen peroxide are added dropwise to the third mixed solution, and the mixture is washed until the pH value is 4 to 7 to obtain a graphene oxide dispersion.
[0029] Among them, the volume of deionized water is 15~25L, the volume of hydrogen peroxide is 2~8L, and the concentration of hydrogen peroxide is 5%.
[0030] The volume of deionized water can be 15L, 18L, 20L, 22L, 25L, and the volume of hydrogen peroxide can be 2L, 3L, 4L, 5L, 6L, 7L, 8L.
[0031] Deionized water and hydrogen peroxide are added dropwise to the third mixed solution, the strong acid is diluted with deionized water, the excess oxidant and the strong acid are preliminarily washed away, and then the mixture is washed with deionized water and hydrochloric acid until the pH value is 4-7 to obtain a graphene oxide dispersion.
[0032] The concentration of the graphene oxide dispersion is 0.5-2 mol / L, for example, the concentration of the graphene oxide dispersion is 0.5 mol / L, 1 mol / L, 1.2 mol / L, 1.5 mol / L, 2 mol / L. In the embodiment of the present application, only the concentration of the graphene oxide dispersion is 1 mol / L as an example for description.
[0033] The pH of the graphene oxide dispersion may be 4, 5, 6, or 7. In the embodiments of the present application, the graphene oxide dispersion having a pH of 5 is used as an example for illustration.
[0034] When washing, first use deionized water and then use hydrochloric acid with a concentration of 5%.
[0035] In the embodiment of the present application, strong acid / strong oxidant is added to fully oxidize the graphite sheet, so that oxygen-containing defects are generated on the graphite surface, thereby gradually increasing the distance between graphite layers until they are completely peeled off to generate graphene oxide. Compared with graphene, graphene oxide has more polar functional groups and can form a uniform dispersion in polar solvents such as water or ethanol, so as to facilitate the subsequent formation of graphene aerogel.
[0036] Step 102: adding magnetic particle powder and single-walled carbon nanotubes into the graphene oxide dispersion to obtain a first mixed solution.
[0037] The mass of the magnetic particle powder is 10-100 g, the mass of the single-walled carbon nanotube is 8-50 g, and the volume of the graphene oxide dispersion is 2-5 L.
[0038] Among them, the mass of the magnetic particle powder can be 10g, 20g, 30g, 40g, 50g, 60g, 70g, 80g, 90g, and 100g, the mass of the single-walled carbon nanotubes can be 8g, 9g, 10g, 15g, 18g, 20g, 25g, 30g, 35g, 40g, 45g, and 50g, and the volume of the graphene oxide dispersion can be 2L, 2.5L, 3L, 3.5L, 4L, 4.5L, and 5L.
[0039] The particle size of the magnetic particle powder is 50-200 nm. For example, the particle size of the magnetic particle powder is 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 180 nm, and 200 nm.
[0040] The magnetic particle powder includes at least one of nano iron powder and ferroferric oxide (Fe3O4) powder. The nano iron powder is ultrafine nano iron powder, and the Fe3O4 powder is ultrafine Fe3O4 powder. In the embodiment of the present application, the magnetic particle powder is only ultrafine nano iron powder as an example for description. The particle size of the ultrafine nano iron powder is 50-100 nm.
[0041] The diameter of the single-walled carbon nanotube is 10-20 nm, for example, the length of the single-walled carbon nanotube is 10 nm, 12 nm, 15 nm, 18 nm, and 20 nm.
[0042] It should be noted that before executing step 102, the magnetic particle powder can be placed in ethanol, hydrochloric acid and distilled water in sequence, and the impurities and oxide layer on the surface can be effectively removed by ultrasonic washing. Then the powder is dried. That is, the magnetic particle powder used in step 102 is the magnetic particle powder after drying.
[0043] The ultrasonic washing time is 10 to 20 minutes, for example, the ultrasonic washing time is 10 minutes, 12 minutes, 15 minutes, 18 minutes, and 20 minutes. In the embodiment of the present application, only the ultrasonic washing time of 15 minutes is used as an example for explanation.
[0044] The temperature of the drying process is 100-150° C. For example, the temperature of the drying process is 100° C., 110° C., 120° C., 130° C., 140° C., 150° C. In the embodiment of the present application, only the drying process temperature of 120° C. is used as an example for description.
[0045] The drying time is 4 to 8 hours, for example, the drying time is 4 hours, 5 hours, 6 hours, 7 hours, and 8 hours. In the embodiment of the present application, only the drying time of 6 hours is used as an example for description.
[0046] After executing step 102, the first mixed solution may be subjected to ultrasonic treatment to uniformly mix the components. The ultrasonic treatment time may be 20 to 40 minutes, for example, the ultrasonic treatment time is 20 minutes, 25 minutes, 30 minutes, 35 minutes, or 40 minutes. In the embodiment of the present application, only 30 minutes of ultrasonic treatment is used as an example for illustration.
[0047] Step 103: Concentrating and freezing the first mixed solution to obtain a first composite material.
[0048] This step can be achieved by following the steps (1) to (3), including: (1) The first mixed solution is concentrated, and the viscosity after concentration is 3000-10000 mPa·S.
[0049] The first mixed liquid can be concentrated by heating, and mechanical stirring can be performed during the concentration process to ensure uniform mixing and achieve the best concentration effect.
[0050] The viscosity after concentration can be 3000mPa·S, 4000mPa·S, 5000mPa·S, 6000mPa·S, 7000mPa·S, 8000mPa·S, 9000mPa·S, 10000mPa·S, which is not specifically limited. In the embodiments of the present application, only the viscosity after concentration of 5000mPa·S is used as an example for description.
[0051] (2) The concentrated first mixed liquid is transferred to a preset plate mold and frozen and shaped by liquid nitrogen.
[0052] The concentrated first mixed liquid is transferred to a preset plate mold with a mold thickness of 2 to 10 mm, and then the mixed liquid transferred to the mold is quickly frozen and formed by liquid nitrogen to maintain its shape and structure stability.
[0053] The mold thickness can be 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, or 10 mm, without specific limitation. In the embodiments of the present application, only the mold thickness of 5 mm is used as an example for illustration. In addition, the shape of the mold can be set and changed as needed, without specific limitation.
[0054] (3) Using a freeze-drying process to remove water from the first mixed solution after freeze-setting to obtain a first composite material.
[0055] The first mixed liquid after freeze-setting is further processed by freeze-drying process to remove water therein, thereby obtaining a composite material with a sponge-like structure, namely, the first composite material.
[0056] In the embodiments of the present application, the process conditions of the freeze-drying process are: vacuum degree of 40~100Pa, freezing temperature of -80℃~-50℃, and cooling rate of 5~15℃ / min.
[0057] The vacuum degree may be 40Pa, 50Pa, 60Pa, 70Pa, 80Pa, 90Pa, or 100Pa, and no specific limitation is given to this. In the embodiment of the present application, only the vacuum degree of 40Pa is used as an example for explanation.
[0058] The freezing temperature may be -80°C, -75°C, -70°C, -65°C, -60°C, -55°C, or -50°C, and is not specifically limited thereto. In the embodiments of the present application, only the freezing temperature of -80°C is used as an example for illustration.
[0059] The cooling rate may be 5°C / min, 8°C / min, 9°C / min, 10°C / min, 12°C / min, 13°C / min, or 15°C / min, and is not specifically limited thereto. In the embodiments of the present application, only a cooling rate of 10°C / min is used as an example for illustration.
[0060] Step 104: performing annealing treatment on the first composite material to obtain a second composite material.
[0061] Wherein, the second composite material is an uncoated graphene aerogel composite material.
[0062] In the embodiment of the present application, the process conditions of the annealing treatment are: annealing temperature is 400~800℃, holding time is 4~8h, and cooling rate is 5~15℃ / min.
[0063] The annealing temperature may be 400° C., 500° C., 600° C., 700° C., or 800° C., and is not specifically limited thereto. In the embodiments of the present application, only the annealing temperature of 600° C. is used as an example for illustration.
[0064] The heat preservation time can be 4h, 5h, 6h, 7h, 8h, which is not specifically limited. In the embodiment of the present application, only the heat preservation time of 6h is used as an example for explanation.
[0065] The cooling rate may be 5°C / min, 8°C / min, 9°C / min, 10°C / min, 12°C / min, 13°C / min, or 15°C / min, without specific limitation. In the embodiments of the present application, only a cooling rate of 10°C / min is used for illustration.
[0066] Step 105: placing the second composite material in a carbonization furnace, heating it for a first time period under a nitrogen atmosphere, and transferring it to a rotary kiln after cooling, wherein the temperature of the rotary kiln is 500-560°C.
[0067] Among them, the heating temperature in the carbonization furnace is 500~650℃, the first time is 4~8h, and the flow rate of nitrogen is 10~20L / min.
[0068] Specifically, the heating temperature in the carbonization furnace may be 500° C., 520° C., 550° C., 580° C., 600° C., 620° C., 650° C., and there is no specific limitation thereto. In the embodiment of the present application, the heating temperature in the carbonization furnace is 580° C. as an example for illustration.
[0069] The temperature of the rotary kiln can be 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, or 560°C.
[0070] It should be noted that the temperature of the rotary kiln is less than or equal to the temperature of the carbonization furnace. In the embodiments of the present application, the example in which the temperature of the rotary kiln is less than the temperature of the carbonization furnace is used for illustration.
[0071] The first duration can be 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, 6.5 hours, 7 hours, 7.5 hours, or 8 hours, and no specific limitation is given to this. In the embodiment of the present application, only the first duration of 6 hours is taken as an example for description.
[0072] The flow rate of nitrogen can be 10 L / min, 12 L / min, 15 L / min, 18 L / min, 20 L / min, which is not specifically limited. In the embodiment of the present application, only the flow rate of nitrogen is 15 L / min as an example for description.
[0073] It should be noted that before the acetylene gas is introduced, the rotary kiln may be evacuated first, and then argon gas may be introduced into the rotary kiln to purify the cavity, and then the kiln may be evacuated again before the acetylene gas is introduced.
[0074] The vacuum degree in the rotary kiln may be 20-60 Pa. For example, the vacuum degree in the rotary kiln is 20 Pa, 30 Pa, 40 Pa, 50 Pa, or 60 Pa.
[0075] The flow rate of argon gas is 10-20 L / min. For example, the flow rate of argon gas can be 10 L / min, 12 L / min, 15 L / min, 18 L / min, 20 L / min, which is not specifically limited. In the embodiment of the present application, only the flow rate of argon gas of 15 L / min is used as an example for description.
[0076] The time for introducing argon gas can be set and changed as needed, and is not specifically limited thereto. For example, the time for introducing argon gas is 5 min, 6 min, 8 min, or 10 min.
[0077] Step 106: introducing acetylene gas into the rotary kiln and reacting for a second time to obtain a graphene composite material.
[0078] The flow rate of the acetylene gas is 1-5 L / min, for example, the flow rate of the acetylene gas is 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min. In the embodiment of the present application, only the flow rate of the acetylene gas is 3 L / min as an example for description.
[0079] The second duration is 6 to 10 hours, for example, the second duration is 6 hours, 7 hours, 8 hours, 9 hours, and 10 hours. In the embodiment of the present application, only the second duration of 8 hours is taken as an example for description.
[0080] The rotary kiln may be a MOCVD (Metal-Organic Chemical Vapor Deposition) rotary kiln.
[0081] In the present application embodiment, graphene and single-walled carbon nanotubes constitute sponge skeleton materials, and magnetic particle powder is filled in the skeleton gap. Wherein, the sponge skeleton pore size is 50~100nm, the particle size of the magnetic particle powder is 50~200nm, the filling rate is 35%~50%, the diameter of the single-walled carbon nanotube is 10~20nm, the outermost layer is covered by an amorphous carbon layer, and the thickness of the carbon layer is about 15nm, which can effectively prevent the skeleton structure from directly contacting water or other corrosive substances, maintain the stability of the internal structure, and enhance the durability and corrosion resistance of the material. In addition, graphene and carbon nanotube skeletons are more stable than single skeleton structures, and single graphene sheet coverage or mixing may cause sheet slippage and even interface failure under the action of mechanical force. Moreover, graphene and carbon nanotubes simultaneously construct a planar and vertical conductive network, which can accelerate the migration of carriers, effectively enhance the dielectric loss of materials, and the fibrous structure of carbon nanotubes can also enhance the diversity of material absorption methods. In addition, the synergistic effect brought by nanoscale magnetic particle powder is conducive to improving the hysteresis loss of the material, and the nanostructure also improves the bonding stability and dispersibility between materials; the porous sponge-like substrate has a large number of pore structures, which is conducive to extending the electromagnetic wave absorption path, improving the electromagnetic wave absorption efficiency, and enhancing the absorption capacity of the material.
[0082] On the other hand, a graphene composite material is provided, which is prepared by the preparation method described above.
[0083] The technical solution of the present application will be described in detail below through specific embodiments.
[0084] In the following specific examples, operations involved without specifying conditions were performed under conventional conditions or conditions recommended by the manufacturer.
[0085] Example 1 Embodiment 1 provides a graphene composite material, which is obtained by the following preparation method: (1) Preparation of graphene oxide dispersion: 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid were mixed and stirred in an ice bath for 1 h. After adding 500 g of potassium permanganate, the mixture was stirred for another 2 h and stored at 30 °C for 0.5 h. 20 L of deionized water and 5 L of 5% hydrogen peroxide were added dropwise, and the graphene oxide dispersion was obtained by repeated washing with deionized water and 5% hydrochloric acid. The concentration of the graphene oxide dispersion was 1 mol / L and the pH was 5.
[0086] (2) 10 g of ultrafine nano-iron powder was placed in ethanol, hydrochloric acid and distilled water in turn, and ultrasonically washed for 15 min to remove impurities and oxide layers on its surface. After cleaning, the powder was dried at 120 °C for 6 h. Subsequently, the dried ultrafine nano-iron powder and 9 g of single-walled carbon nanotubes were added to 3 L of graphene oxide dispersion.
[0087] (3) Ultrasonic treatment for 30 min, followed by mechanical stirring and concentration while stirring, so that the viscosity of the mixed solution reaches 5000 mPa·s.
[0088] (4) The concentrated mixed liquid is transferred to a specific plate mold, and the mixed liquid in the mold is quickly frozen and shaped using liquid nitrogen.
[0089] (5) The frozen material is placed in a freeze dryer with a freezing temperature of -80°C, a vacuum degree of 40 Pa, a cooling rate of 10°C / min, and the composite material is taken out at a constant temperature and pressure for 48 hours. At this time, the composite material is completely free of internal moisture.
[0090] (6) The composite material was annealed at a temperature of 600°C, a holding time of 6 hours, and a cooling rate of 10°C / min. After the annealing treatment, an uncoated graphene aerogel composite material was obtained.
[0091] (7) The graphene aerogel composite material was placed in a carbonization furnace, the vacuum degree was evacuated to 40 Pa, and heated at 580 °C for 6 h in a nitrogen atmosphere with a nitrogen flow rate of 15 L / min. After cooling, it was transferred to a MOCVD furnace with a temperature of 540 °C.
[0092] (8) The MOCVD furnace was first evacuated to 40 Pa, and argon gas was introduced into the purification chamber at a flow rate of 15 L / min. After 5 minutes, the vacuum was evacuated to 40 Pa, and acetylene gas was introduced at a flow rate of 3 L / min. The reaction time was 8 hours to obtain an amorphous carbon-coated graphene composite material.
[0093] Example 2 Embodiment 2 provides a graphene composite material, which is obtained by the following preparation method: (1) Preparation of graphene oxide dispersion: 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid were mixed and stirred in an ice bath for 1 h. After adding 500 g of potassium permanganate, the mixture was stirred for another 2 h and stored at 30 °C for 0.5 h. 20 L of deionized water and 5 L of 5% hydrogen peroxide were added dropwise, and the graphene oxide dispersion was obtained by repeated washing with deionized water and 5% hydrochloric acid. The concentration of the graphene oxide dispersion was 1 mol / L and the pH was 5.
[0094] (2) 20 g of ultrafine nano-iron powder was placed in ethanol, hydrochloric acid and distilled water in turn, and ultrasonically washed for 15 min to remove impurities and oxide layers on its surface. After cleaning, the powder was dried at 120 °C for 6 h. Subsequently, the dried ultrafine nano-iron powder and 18 g of single-walled carbon nanotubes were added to 3 L of graphene oxide dispersion.
[0095] (3) Ultrasonic treatment for 30 min, followed by mechanical stirring and concentration while stirring, so that the viscosity of the mixed solution reaches 5000 mPa·s.
[0096] (4) The concentrated mixed liquid is transferred to a specific plate mold, and the mixed liquid in the mold is quickly frozen and shaped using liquid nitrogen.
[0097] (5) The frozen material is placed in a freeze dryer with a freezing temperature of -80°C, a vacuum degree of 40 Pa, a cooling rate of 10°C / min, and the composite material is taken out at a constant temperature and pressure for 48 hours. At this time, the composite material is completely free of internal moisture.
[0098] (6) The composite material was annealed at a temperature of 600°C, a holding time of 6 hours, and a cooling rate of 10°C / min. After the annealing treatment, an uncoated graphene aerogel composite material was obtained.
[0099] (7) The graphene aerogel composite material was placed in a carbonization furnace, the vacuum degree was evacuated to 40 Pa, and heated at 580 °C for 6 h in a nitrogen atmosphere with a nitrogen flow rate of 15 L / min. After cooling, it was transferred to a MOCVD furnace with a temperature of 540 °C.
[0100] (8) The MOCVD furnace was first evacuated to 4 Pa, and argon gas was introduced into the purification chamber at a flow rate of 15 L / min. After 5 minutes, the vacuum was evacuated to 40 Pa, and acetylene gas was introduced at a flow rate of 3 L / min. The reaction time was 8 hours to obtain an amorphous carbon-coated graphene composite material.
[0101] Example 3 Embodiment 3 provides a graphene composite material, which is obtained by the following preparation method: (1) Preparation of graphene oxide dispersion: 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid were mixed and stirred in an ice bath for 1 h. After adding 500 g of potassium permanganate, the mixture was stirred for another 2 h and stored at 30 °C for 0.5 h. 20 L of deionized water and 5 L of 5% hydrogen peroxide were added dropwise, and the graphene oxide dispersion was obtained by repeated washing with deionized water and 5% hydrochloric acid. The concentration of the graphene oxide dispersion was 1 mol / L and the pH was 5.
[0102] (2) 50 g of ultrafine nano-iron powder was placed in ethanol, hydrochloric acid and distilled water in turn, and ultrasonically washed for 15 min to remove impurities and oxide layers on its surface. After cleaning, the powder was dried at 120 °C for 6 h. Subsequently, the dried ultrafine nano-iron powder and 36 g of single-walled carbon nanotubes were added to 3 L of graphene oxide dispersion.
[0103] (3) Ultrasonic treatment for 30 min, followed by mechanical stirring and concentration while stirring, so that the viscosity of the mixed solution reaches 5000 mPa·s.
[0104] (4) The concentrated mixed liquid is transferred to a specific plate mold, and the mixed liquid in the mold is quickly frozen and shaped using liquid nitrogen.
[0105] (5) The frozen material is placed in a freeze dryer with a freezing temperature of -80°C, a vacuum degree of 40 Pa, a cooling rate of 10°C / min, and the composite material is taken out at a constant temperature and pressure for 48 hours. At this time, the composite material is completely free of internal moisture.
[0106] (6) The composite material was annealed at a temperature of 600°C, a holding time of 6 hours, and a cooling rate of 10°C / min. After the annealing treatment, an uncoated graphene aerogel composite material was obtained.
[0107] (7) The graphene aerogel composite material was placed in a carbonization furnace, the vacuum degree was evacuated to 40 Pa, and heated at 580 °C for 6 h in a nitrogen atmosphere with a nitrogen flow rate of 15 L / min. After cooling, it was transferred to a MOCVD furnace with a temperature of 540 °C.
[0108] (8) The MOCVD furnace was first evacuated to 4 Pa, and argon gas was introduced into the purification chamber at a flow rate of 15 L / min. After 5 minutes, the vacuum was evacuated to 40 Pa, and acetylene gas was introduced at a flow rate of 3 L / min. The reaction time was 8 hours to obtain an amorphous carbon-coated graphene composite material.
[0109] Example 4 Embodiment 4 provides a graphene composite material, which is obtained by the following preparation method: (1) Preparation of graphene oxide dispersion: 150 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid were mixed and stirred in an ice bath for 1 h. After adding 500 g of potassium permanganate, the mixture was stirred for another 2 h and stored at 30 °C for 0.5 h. 20 L of deionized water and 5 L of 5% hydrogen peroxide were added dropwise, and the graphene oxide dispersion was obtained by repeated washing with deionized water and 5% hydrochloric acid. The concentration of the graphene oxide dispersion was 1 mol / L and the pH was 5.
[0110] (2) 50 g of ultrafine nano-iron powder was placed in ethanol, hydrochloric acid and distilled water in turn, and ultrasonically washed for 15 min to remove impurities and oxide layers on its surface. After cleaning, the powder was dried at 120 °C for 6 h. Subsequently, the dried ultrafine nano-iron powder and 18 g of single-walled carbon nanotubes were added to 3 L of graphene oxide dispersion.
[0111] (3) Ultrasonic treatment for 30 min, followed by mechanical stirring and concentration while stirring, so that the viscosity of the mixed solution reaches 5000 mPa·s.
[0112] (4) The concentrated mixed liquid is transferred to a specific plate mold, and the mixed liquid in the mold is quickly frozen and shaped using liquid nitrogen.
[0113] (5) The frozen material is placed in a freeze dryer with a freezing temperature of -80°C, a vacuum degree of 40 Pa, a cooling rate of 10°C / min, and the composite material is taken out at a constant temperature and pressure for 48 hours. At this time, the composite material is completely free of internal moisture.
[0114] (6) The composite material was annealed at a temperature of 600°C, a holding time of 6 hours, and a cooling rate of 10°C / min. After the annealing treatment, an uncoated graphene aerogel composite material was obtained.
[0115] (7) The graphene aerogel composite material was placed in a carbonization furnace, the vacuum degree was evacuated to 40 Pa, and heated at 580 °C for 6 h in a nitrogen atmosphere with a nitrogen flow rate of 15 L / min. After cooling, it was transferred to a MOCVD furnace with a temperature of 540 °C.
[0116] (8) The MOCVD furnace was first evacuated to 4 Pa, and argon gas was introduced into the purification chamber at a flow rate of 15 L / min. After 5 minutes, the vacuum was evacuated to 40 Pa, and acetylene gas was introduced at a flow rate of 3 L / min. The reaction time was 8 hours to obtain an amorphous carbon-coated graphene composite material.
[0117] Example 5 Embodiment 5 provides a graphene composite material, which is obtained by the following preparation method: (1) Preparation of graphene oxide dispersion: 150 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid were mixed and stirred in an ice bath for 1 h. After adding 500 g of potassium permanganate, the mixture was stirred for another 2 h and stored at 30 °C for 0.5 h. 20 L of deionized water and 5 L of 5% hydrogen peroxide were added dropwise, and the graphene oxide dispersion was obtained by repeated washing with deionized water and 5% hydrochloric acid. The concentration of the graphene oxide dispersion was 1 mol / L and the pH was 5.
[0118] (2) 100 g of ultrafine nano-iron powder was placed in ethanol, hydrochloric acid and distilled water in turn, and ultrasonically washed for 15 min to remove impurities and oxide layers on its surface. After cleaning, the powder was dried at 120 °C for 6 h. Subsequently, the dried ultrafine nano-iron powder and 18 g of single-walled carbon nanotubes were added to 3 L of graphene oxide dispersion.
[0119] (3) Ultrasonic treatment for 30 min, followed by mechanical stirring and concentration while stirring, so that the viscosity of the mixed solution reaches 5000 mPa·s.
[0120] (4) The concentrated mixed liquid is transferred to a specific plate mold, and the mixed liquid in the mold is quickly frozen and shaped using liquid nitrogen.
[0121] (5) The frozen material is placed in a freeze dryer with a freezing temperature of -80°C, a vacuum degree of 40 Pa, a cooling rate of 10°C / min, and the composite material is taken out at a constant temperature and pressure for 48 hours. At this time, the composite material is completely free of internal moisture.
[0122] (6) The composite material was annealed at a temperature of 600°C, a holding time of 6 hours, and a cooling rate of 10°C / min. After the annealing treatment, an uncoated graphene aerogel composite material was obtained.
[0123] (7) The graphene aerogel composite material was placed in a carbonization furnace, the vacuum degree was evacuated to 40 Pa, and heated at 580 °C for 6 h in a nitrogen atmosphere with a nitrogen flow rate of 15 L / min. After cooling, it was transferred to a MOCVD furnace with a temperature of 540 °C.
[0124] (8) The MOCVD furnace was first evacuated to 4 Pa, and argon gas was introduced into the purification chamber at a flow rate of 15 L / min. After 5 minutes, the vacuum was evacuated to 40 Pa, and acetylene gas was introduced at a flow rate of 3 L / min. The reaction time was 8 hours to obtain an amorphous carbon-coated graphene composite material.
[0125] Comparative Example The comparative example provides a graphene material, which is obtained by the following preparation method: (1) Preparation of graphene oxide dispersion: 300 g of graphite powder, 100 g of sodium nitrate, and 1.5 L of 98% concentrated sulfuric acid were mixed and stirred in an ice bath for 1 h. After adding 500 g of potassium permanganate, the mixture was stirred for another 2 h and stored at 30 °C for 0.5 h. 20 L of deionized water and 5 L of 5% hydrogen peroxide were added dropwise, and the graphene oxide dispersion was obtained by repeated washing with deionized water and 5% hydrochloric acid. The concentration of the graphene oxide dispersion was 1 mol / L and the pH was 5.
[0126] (2) 3 L of graphene oxide dispersion was ultrasonically treated for 30 min, and then mechanically stirred. During the stirring, the mixture was concentrated so that the viscosity of the mixture reached 5000 mPa·s.
[0127] (3) The concentrated mixed liquid is transferred to a specific plate mold, and the mixed liquid in the mold is quickly frozen and shaped using liquid nitrogen.
[0128] (4) Place the frozen material into a freeze dryer with a freezing temperature of -80°C, a vacuum degree of 40Pa, a cooling rate of 10°C / min, and maintain constant temperature and pressure for 48 hours before taking out the material. At this time, the internal moisture of the material is completely removed.
[0129] (5) The material was annealed at 600 °C, holding time of 6 h, and cooling rate of 10 °C / min.
[0130] (6) The annealed material was placed in a carbonization furnace, the vacuum degree was evacuated to 40 Pa, and heated at 580 °C for 6 h in a nitrogen atmosphere with a nitrogen flow rate of 15 L / min. After cooling, it was transferred to a MOCVD furnace with a temperature of 540 °C.
[0131] (7) The MOCVD furnace was first evacuated to 4 Pa, and argon gas was introduced into the purification chamber at a flow rate of 15 L / min. After 5 minutes, the vacuum was evacuated to 40 Pa, and acetylene gas was introduced at a flow rate of 3 L / min. The reaction time was 8 hours to obtain graphene material.
[0132] It should be noted that, compared with Example 1, Example 2 improves the quality of magnetic particle powder and single-walled carbon nanotubes. Compared with Example 2, Example 3 improves the quality of magnetic particle powder and single-walled carbon nanotubes. Compared with Example 3, Example 4 reduces the quality of graphite powder and single-walled carbon nanotubes. Compared with Example 4, Example 5 improves the quality of magnetic particle powder. Compared with Examples 1 to 5, only graphene oxide dispersion is added in the comparative example, and magnetic particle powder and single-walled carbon nanotubes are not added.
[0133] See also Figure 2 and Figure 3 , Figure 2 This is a TEM (Transmission Electron Microscope) morphology of the graphene material prepared in the comparative example. Figure 3 TEM morphology of the graphene composite material prepared in Example 3. Figure 2 and Figure 3 It can be seen that a single graphene is a sheet structure. After the graphene is compounded with single-walled carbon nanotubes and magnetic particle powder, a sponge skeleton structure is formed, the magnetic particle powder fills the gaps in the skeleton, and the outermost layer is covered by an amorphous carbon layer.
[0134] Application Examples The complex permittivity and permeability of the material in the frequency band of 2 GHz to 18 GHz were tested according to ASTM D7449 / D7449M-22a "Standard test method for relative complex permittivity and relative permeability of solid materials at microwave frequencies using coaxial air lines". The sample size was a coaxial ring with an outer diameter of 7 mm and an inner diameter of 3.04 mm, and the material thickness was 2 mm to 3 mm.
[0135] The reflectivity of the material in the 2GHz~18GHz frequency band was tested according to GJB2038A-2011 “Test Method for Reflectivity of Radar Absorbing Materials”, and the sample size was 300mm×300mm×5mm.
[0136] The reflectivity, complex dielectric constant and relative magnetic permeability of the materials provided in Examples 1 to 5 and the comparative examples were tested. The test results are shown in Figures 4 to 8 .from Figures 4 to 8 It can be seen that the reflectivity of the graphene composite material prepared in Example 5 is less than -5dB in the range of 3~18GHz, and it has the best wave absorbing performance. This is because the graphene composite material prepared in this example has the lowest complex dielectric constant and the highest magnetic permeability, which is most in line with the impedance matching principle, and therefore has the best wave absorbing performance. The graphene composite material prepared in Example 3 has good wave absorbing performance at low frequencies. This is because the graphene composite material of this example has the highest complex dielectric constant, which is conducive to the absorption peak moving to low frequencies. The performance of the comparative example is the worst. This is because the content of dielectric loss type material in the comparative example is the lowest, and it does not contain magnetic loss type material.
[0137] The above description is only for the purpose of facilitating those skilled in the art to understand the technical solution of the present application and is not intended to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a graphene composite material, characterized in that: The preparation method comprises: preparing a graphene oxide dispersion; Adding magnetic particle powder and single-walled carbon nanotubes into the graphene oxide dispersion to obtain a first mixed solution; Concentrating and freezing the first mixed solution to obtain a first composite material; annealing the first composite material to obtain a second composite material; The second composite material is placed in a carbonization furnace, heated for a first time under a nitrogen atmosphere, and transferred to a rotary kiln after cooling, wherein the temperature of the rotary kiln is 500-560° C.; Acetylene gas is introduced into the rotary kiln, and after reacting for a second time period, a graphene composite material is obtained.
2. The preparation method according to claim 1, characterized in that: The method for preparing the graphene oxide dispersion comprises: Mixing graphite powder, sodium nitrate and concentrated sulfuric acid, and stirring in an ice bath to obtain a second mixed solution; adding potassium permanganate to the second mixed solution to obtain a third mixed solution; Deionized water and hydrogen peroxide are added dropwise to the third mixed solution, and the mixture is washed until the pH value is 4 to 7 to obtain the graphene oxide dispersion.
3. The preparation method according to claim 2, characterized in that: The mass of the graphite powder is 100-500 g, the mass of the sodium nitrate is 50-200 g, the volume of the concentrated sulfuric acid is 1-3 L, the mass of the potassium permanganate is 300-600 g, the volume of the deionized water is 15-25 L, and the volume of the hydrogen peroxide is 2-8 L.
4. The preparation method according to claim 1, characterized in that: The first mixed solution is concentrated and frozen to obtain a first composite material, comprising: Concentrating the first mixed solution, wherein the viscosity after concentration is 3000-10000 mPa·S; The concentrated first mixed liquid is transferred to a preset plate mold and frozen and formed by liquid nitrogen; The first composite material is obtained by removing moisture from the first mixed solution after freeze-setting using a freeze-drying process.
5. The preparation method according to claim 4, characterized in that: The process conditions of the freeze-drying process are: vacuum degree of 40~100Pa, freezing temperature of -80~-50°C, and cooling rate of 5~15°C / min.
6. The preparation method according to claim 1, characterized in that: The process conditions of the annealing treatment are: annealing temperature is 400-800°C, holding time is 4-8h, and cooling rate is 5-15°C / min.
7. The preparation method according to claim 1, characterized in that: The mass of the magnetic particle powder is 10-100 g, the mass of the single-walled carbon nanotube is 8-50 g, and the volume of the graphene oxide dispersion is 2-5 L.
8. The preparation method according to claim 1, characterized in that: The magnetic particle powder includes at least one of nano iron powder and ferroferric oxide powder.
9. The preparation method according to claim 1, characterized in that: The heating temperature in the carbonization furnace is 500-650° C., and the first time is 4-8 hours; The flow rate of the acetylene gas is 1-5 L / min, and the second time length is 6-10 hours.
10. A graphene composite material, characterized in that: The graphene composite material is prepared by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method for carbon nano tube / oxidized grapheme / nanometer Fe3O4 sandwich hybrid wave absorbing thin films
CN103813699A
Preparation method of green electromagnetic shielding building material
CN111943274A
Preparation method of graphene / carbon nanotube / ferroferric oxide composite material for heat conduction and electromagnetic shielding
CN116828832A
Carbon nanotube hybrid material fabric, composite fabric, and personal protective apparel and equipment
WO2019014212A1
AU2020102002A4